Muammad's Conversations with the Bedouin: A Speech-Act Analysis of Prophetic Discourse in Hadith - Mohd Faizal Kasmani; Yusoff S.H.; Kanaker O. (Brill Academic Publishers, 2024)
Indexed by WOS/ Scopus